Educational Aspirations among the Students of Manipur University, India - Meinam, Martina; Ojha, Sekhar Nath; Singh, Yumlembam Jackie; Lahiri, Biswajit; Meinam, Teresa (Indian Journal of Extension Education, 2023)
Educational aspirations provide students valuable insights that can inform educational policies, improve career guidance, promote equitable opportunities leading to better educational outcomes, and increase success in students’ future careers. This study examined the educational aspirations of students in 2021 at Manipur University, India. A structured interview schedule was designed, and data were collected from 160 students through stratified random sampling from five Schools of studies of the postgraduate students of the University. Students in the School of Human and Environmental Sciences showed the highest Achievement Likelihood of Educational Aspiration Index (ALEAI). Study reveals that the majority of the students wanted to pursue higher education. Students’ primary career advice was found to be their interests. Students were also motivated about their career choice mainly by their parents’ support, followed by the influence of TV, radio, social media, and other media. Students should also be encouraged and empowered to decide on and stand for their right career. The study suggests that it is necessary to review the influences, programmes, and different factors affecting students at all stages of their education.
Keywords: Students Aspirations; Education; Career; Manipur